Recruitment, retention, and adherence of family caregivers: Lessons from a multisite trial - Rueda Díaz, Leidy Johanna; de Souza Guedes, Erika; Lopes Monteiro da Cruz, Diná de Almeida (Investigación y Educación en Enfermería, 2023)
Objective. To describe the recruitment, retention of family caregivers, and adherence to a telephone based intervention evaluated in a multi-site trial and provide recommendations for the design of future studies. Methods. A descriptive study based on a secondary analysis of a multi-site clinical development in Colombia and Brazil. Recruitment was measured by the number of participants eligible and consented. Retention was assessed by the percentage of participants with outcomes data at two follow-ups. The intervention adherence was measured by the percentage of the caregiver who received the intervention. Results. Of the family caregivers assessed, 63% were eligible, and 32.9% declined to be in the study for time restriction or no interest. In Colombia, the total retention rate of caregivers was 63.4% at the first follow-up and 48% at the second follow-up, while in Brazil was de 52.8% and 46.2%, respectively. At the end of the study, the sample comprised 28 and 70 caregivers in the intervention and control groups, respectively, for a retention rate of 47%. Of 104 family caregivers allocated to the intervention group, 42 (40.3%) received five sessions. Most reported not completing the Caregiver´s Activity Diary. Conclusion. The recruitment of family caregivers, participant retention, and adherence to the telephone intervention was unsuccessful. Future studies should apply an assessment tool during the recruitment of family caregivers and replace the term "caregiver" with "care provider"; in the material involved in the research; define a retention protocol before starting the study and involve family caregivers in the design of the interventions.